2005
DOI: 10.1515/sg-2005-0005
|View full text |Cite
|
Sign up to set email alerts
|

Variation and Correlations Among Stem Growth and Wood Traits of Calycophyllum spruceanum Benth. from the Peruvian Amazon

Abstract: Calycophyllum spruceanum Benth. is an important tree for timber and energy in the western Amazon, with expanding national and international markets for its wood. There is relatively little information, however, about geographic variation in tree growth and wood properties, and correlations among these traits. The first provenance trial was established with farming communities in the Peruvian Amazon. Seven provenances, sampled from regions near the equator, were tested in three planting zones located in one wat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
15
3
3

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 15 publications
4
15
3
3
Order By: Relevance
“…Variation in growth traits due to families within provenances was consistently greater and variation due to provenances was generally greater in the faster-growing plantations. Similar results were reported for this test at 12 months (ROCHON et al, 2007) and for two tests of C. spruceanum in the Peruvian Amazon (SOTELO MONTES et al, 2003;WEBER and SOTELO MONTES, 2005;SOTELO MONTES et al, 2006). However, this was not the case in a test of G. crinita provenances sampled from several different watersheds in the Peruvian Amazon and established in the Aguaytía watershed (WEBER and SOTELO MONTES, 2008).…”
Section: Genetic and Environmental Variation In Tree Height And Stem supporting
confidence: 84%
See 1 more Smart Citation
“…Variation in growth traits due to families within provenances was consistently greater and variation due to provenances was generally greater in the faster-growing plantations. Similar results were reported for this test at 12 months (ROCHON et al, 2007) and for two tests of C. spruceanum in the Peruvian Amazon (SOTELO MONTES et al, 2003;WEBER and SOTELO MONTES, 2005;SOTELO MONTES et al, 2006). However, this was not the case in a test of G. crinita provenances sampled from several different watersheds in the Peruvian Amazon and established in the Aguaytía watershed (WEBER and SOTELO MONTES, 2008).…”
Section: Genetic and Environmental Variation In Tree Height And Stem supporting
confidence: 84%
“…Hook. f. ex K. Shum (SOTELO MONTES et al, 2003;WEBER and SOTELO MONTES, 2005;SOTELO MONTES et al, 2006); Prosopis flexuosa D.C. (CONY, 1996); Sterculia apetala (Jacq.) Karst (DVORAK et al, 1998); Vochysia guatemalensis Sm., J. D. (CORNELIUS and MESÉN, 1997)].…”
Section: Genetic and Environmental Variation In Tree Height And Stem mentioning
confidence: 99%
“…Adult trees (age unknown) in natural stands can attain heights of 35 m with stem diameters of 1.8 m at breast height (SEARS, 2003). The wood is diffuse-porous, with a basic density of 740 kg/m 3 for mature wood (age unknown) in natural stands (measured at 1.3 m above ground; KEENAN and TEJADA, 1984) and 563 kg/m 3 at 32 months of age in plantations (measured from 35 to 65 cm above ground, WEBER and SOTELO MONTES, 2005). It is generally assumed that mature wood is formed after 15-20 years in natural stands, but this has not been confirmed by studies.…”
Section: Genetic Variation and Correlations Between Growth And Wood Dmentioning
confidence: 99%
“…The first provenance test of C. spruceanum established in Peru demonstrated that plantation yield could be increased by selecting fast-growing provenances (SOTELO MONTES et al, 2003;WEBER and SOTELO MONTES, 2005). However, phenotypic correlations between growth and wood density differed in sign among planting zones, suggesting that selection of fast-growing provenances may produce wood with lower density in some zones and higher density in other zones.…”
Section: Genetic Variation and Correlations Between Growth And Wood Dmentioning
confidence: 99%
“…Em plantios de C. spruceanum com idade de 16, 28 e 39 meses (SOTELO MONTES et al, 2006;2007) e aos 32 meses (WEBER; SOTELO MONTES, 2005) foi evidenciado, com base na avaliação das propriedades tecnológicas, o potencial da espécie em produzir madeira em idades jovens. Por sua vez, Gutiérrez e Ramos (2013) identificaram o potencial da espécie para estudos dendrocronológicos na Amazônia peruana, destacando que os anéis de crescimento são delimitados por zonas fibrosas mais estreitas radialmente.…”
Section: Introductionunclassified